Effects of High-Fructose Diets on Central Appetite Signaling and Cognitive Function - Lowette, Katrien; Roosen, Lina; Tack, Jan; Vanden Berghe, Pieter (Frontiers in Nutrition, 2015)
The consumption of fructose has increased tremendously over the last five decades, which is to a large extent due to the development of high fructose corn syrup (HFCS), a commercial sugar additive that contains high amounts of free fructose. HFCS is often added to processed food and beverages partly because it is a powerful sweetener but even more so because the production is cheap. Although fructose in combination with fiber, vitamins and minerals, as present in fruits, is a healthy source of energy, isolated fructose, in processed food products has been associated with several health disorders such as insulin resistance and hypertension. Apart from its metabolic consequences, a growing body of literature suggests that free fructose can also affect neuronal systems. High fructose intake may on the one hand affect central appetite regulation by altering specific components of the endocannabinoid system. On the other hand it appears to impact on cognitive function by affecting phosphorylation levels of insulin receptor, synapsin 1 and synaptophysin. The present report reviews the recent evidence showing a negative effect of free fructose consumption on central appetite control, as well as cognitive function.